Isolated vocal cord palsy secondary to a paraoesophageal hiatus hernia: a rare variant of Ortner's syndrome. Issue 11 (15th November 2022) - Dolan, Sean; McArthur, Claire; Buchanan, Malcolm A
Abstract : Dysphonia is a common presenting symptom to the outpatient ear, nose and throat team and the need to have a systematic approach to its investigation and management is imperative. Red flag features combined with clinical examination including flexible nasoendoscopy will help to identify laryngeal causes of dysphonia. Vocal cord palsy can have both laryngeal and extralaryngeal aetiologies including Ortner's syndrome. We present a case where a woman in her 70s was referred with persistent hoarseness, found to have an isolated vocal cord palsy with CT scan revealing a very large hiatus hernia producing mass effect at the aortopulmonary window with no other pathology identified. To our knowledge, this is the second case in the literature of a hiatus hernia causing a vocal cord palsy. This case underpins the need for prompt assessment by flexible laryngoscopy, and consideration of extralaryngeal causes of vocal cord palsy during a dysphonia assessment.